PERKEMBANGAN EKSPOR NON-MIGAS PROVINSI JAWA TIMUR PERIODE 2013-2017 - Dhimas Akbar Priambodo; Ahmad Zafrullah Tn; Bambang Budiarto (Jurnal Ekonomi dan Bisnis, 2019)
This study aims to analyze the development of non-oil and gas exports in East Java Province, seen from the value of non-oil exports and the 10 main commodities of non-oil and gas exports over a period of 5 years (2013-2017) and also seen from the intense competition in the international market. This study uses a qualitative descriptive method that describes the conditions of non-oil export in East Java Province. The data used in this study are East Java Province non-oil and gas export data from 2013 to 2017 obtained from existing sources, such as government agencies and various literatures. The results showed that the development of East Java province’s non-oiland gas exports in the 2013-2017 period showed a large increase, as did the exports of the 10 main non-oil and gas export commodities also tended to increase for 5 years. The obstacles that occur in the non-oil exports of East Java Province are mostly due to the sluggish international market and other obstacles that occur in the export areas of East Java Province. Opportunities to increase non-oil and gas exports can be done by maximizing natural resources and human resources as well as government policies of East Java Province.